The Short Story in Peru, 2015-2017 - De Taboada Amat y León, Javier (2018)
The following article reviews a group of 30 short story collections published in Peru between 2015 and 2017. It takes into account the characteristics of the editions, the organization of contents, the most prevalent topics and some motifs or metaphors which recur in several of the collections.